Alpha-actinin binding kinetics modulate cellular dynamics and force generation - Allen J. Ehrlicher; Ramaswamy Krishnan; Ming Guo; Cécile M. Bidan; David A. Weitz; Martin R. Pollak (2015)
Significance In this study, we examine how proteins that cross-link actin filaments control certain biophysical aspects of living cells. We studied α-actinin-4 (ACTN4) a dimeric rod-shaped homodimer, of particular interest because mutations in its actin binding domain cause a human disease characterized by dysfunction of the kidney’s glomeruli; however, the mechanical impact of such mutations are unknown. We find that the human disease-causing K255E mutation in ACTN4 leads to a change in cellular biophysical properties, increasing the affinity for actin increases cellular forces and work, while decreasing cell movement. These observations describe the effects of variable cross-linking on cellular forces and dynamics, and reveal how pathology may arise mechanically from disruptive point mutations in cytoskeletal proteins.